O Retrato Atual das Unidades de Conservação de Uso Sustentável no Estado de Pernambuco - Rêgo, Ananda do Nascimento; Araújo, Bianca Gonzaga de; Lima, Renata Bezerra de Moura; Telino Júnior, Wallace Rodrigues; Lyra-Neves, Rachel Maria de (Scientific Journal ANAP, 2025)
Objective – This study analyzed the Sustainable Use Conservation Units (CUs) in the state of Pernambuco, categorizing them by types, protected biomes, and management tools, such as management plans and advisory councils.Methodology – The research, descriptive and exploratory in nature, was conducted in three main stages: (1) a bibliographic review of scientific articles, legislation, and governmental documents; (2) data collection from the State Environmental Agency (CPRH), applying filters to identify state and municipal CUs, associated biomes, and the existence of management tools; and (3) organization and analysis of the data in tables and charts for clear and accessible visualization.Originality/Relevance – The study addresses gaps in the management and territorial distribution of CUs in Pernambuco, emphasizing the need for greater protection of the Caatinga biome within public environmental policies.Results – Pernambuco has 48 state and 28 municipal sustainable use CUs. However, the Caatinga biome is underrepresented, and there are significant challenges in implementing management tools, such as management plans and advisory councils.Theoretical/Methodological Contributions – The study highlights the importance of strengthening participatory management in CUs through the implementation of advisory councils and management plans, as well as expanding protection for underrepresented biomes.Social and Environmental Contributions – CUs play a crucial role in biodiversity conservation, environmental balance, and achieving the Sustainable Development Goals, generating social, economic, and ecological benefits.
Keywords: Environmental public policies; Environmental Management; Biodiversity